Jorge Luis Borges y la otredad inquietante - Poe Lang, Karen (2007)
The purpose of this article is to examine the relation between literature and philosophy, inside Jorge Luis Borge’s writings. I propose that the way in which Borges read’s the philosophical text, among other texts, was an essential condition of his literary theory. From a close reading of Discusion (book formed with texts written between 1928 and 1932) it is possible to prove that the main ideas of poststructural literary criticism -text, intertextuality, to read/to write- were theorized very early by Borges.